Ensuring numerical stability of wave propagation by tuning model parameters using genetic algorithms and response surface methods. (May 2018) - Rota Roselli, Riccardo Angelini; Vernengo, Giuliano; Altomare, Corrado; Brizzolara, Stefano; Bonfiglio, Luca; Guercio, Roberto
Abstract: The effectiveness of a Metamodel-Embedded Evolution Framework for model parameter identification of a Smoothed Particles Hydrodynamic (SPH) solver, called DualSPHysics, is demonstrated when applied to the generation and propagation of progressive ocean waves. DualSPHysics is an open-source code that provides GP-GPU acceleration, allowing for highly refined simulations. The automatic optimization framework combines the global-convergence capabilities of a Multi-Objective Genetic Algorithm (MOGA) with Response Surface Method (RSM) based on a Kriging approximation. The proposed Metamodel-Embedded Evolutionary framework is used to find the set of SPH model parameters that ensures an accurate reproduction of a 2 n d order Stokes wave propagating in a numeric flume tank. In order to demonstrate the consistency of the obtained results, the optimum set of parameters found by the framework is finally used to reproduce other 2 n d and 3 r d order Stokes waves propagating over the same flume tank.